2023
DOI: 10.1111/tpj.16215
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of allosteric effectors and post‐translational modifications in the control of plant central carbon metabolism

Abstract: SUMMARY Plant metabolism is finely orchestrated to allow the occurrence of complementary and sometimes opposite metabolic pathways. In part this is achieved by the allosteric regulation of enzymes, which has been a cornerstone of plant research for many decades. The completion of the Arabidopsis genome and the development of the associated toolkits for Arabidopsis research moved the focus of many researchers to other fields. This is reflected by the increasing number of high‐throughput proteomic studies, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 231 publications
(369 reference statements)
0
4
0
Order By: Relevance
“…In addition, the primary metabolism of the plants also changed after inoculation with B. velezensis SAAS-63. Carbon metabolism includes starch and sucrose metabolism, glycolysis, and the tricarboxylic acid cycle (Hartman et al 2023 ). Trehalose metabolism is a branch of starch and sucrose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the primary metabolism of the plants also changed after inoculation with B. velezensis SAAS-63. Carbon metabolism includes starch and sucrose metabolism, glycolysis, and the tricarboxylic acid cycle (Hartman et al 2023 ). Trehalose metabolism is a branch of starch and sucrose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the DEGs encoding PEPC and PEPCK were upregulated under NH 4 + treatment and downregulated after HCO 3 − was added (Figure 5). PEPC catalyzes the carboxylation of PEP in the presence of HCO 3 − to form OAA, and PEPCK catalyzes the decarboxylation of OAA to PEP in the gluconeogenesis pathway [86]. Therefore, the higher expression of PEPC and PEPCK under NH 4 + conditions could lead to futile cycling between PEP and OAA in the cytoplasm, resulting in a lower accumulation of OAA in the roots (Table 3), which decreases the C anaplerosis in the TCA cycle.…”
Section: Supplementing With Hcomentioning
confidence: 99%
“…Plant biochemistry focuses on understanding the kinetics, structure and regulatory mechanisms that govern enzymes and metabolic pathways in plants ( Hartman et al, 2023 ). This historical approach is essential to understand biological processes in detail and is the foundation of rational strategies in metabolic engineering and synthetic biology for crop improvement ( Wurtzel et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of useful tools are BRENDA ( Chang et al 2021 ), Plant PTM viewer ( Willems et al 2019 ), PhosPhat ( Durek et al 2010 ), BAR ( Winter et al 2007 ), and TAIR ( Huala et al 2001 ). This gives plant biochemists enormous potential to explore novel modes of metabolic regulation in combination with other biochemical techniques ( Hartman et al 2023 ). A pipeline to translate the biochemical knowledge to metabolic engineering research would start with pure preparations of the enzymes and mutant versions that mimic the PTMs to clearly understand their regulation.…”
Section: Introductionmentioning
confidence: 99%